Pregnancy outcomes in patients with psoriasis, psoriatic arthritis, or axial spondyloarthritis receiving ixekizumab - A. Egeberg; L. Iversen; A. B. Kimball; S. Kelly; E. Grace; H. Patel; W. Xu; G. Gallo; E. Riedl; S. R. Feldman (Journal of Dermatological Treatment)
Background Psoriasis, psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) are chronic inflammatory diseases that often affect women of childbearing age. Detailed information about pregnancy and related outcomes across these indications in patients exposed to ixekizumab is lacking.Objectives To evaluate pregnancy outcomes after maternal or paternal exposure to ixekizumab in patients with psoriasis, PsA, or axSpA.Methods Pregnancy cases from clinical trials and post-marketing reports, associated with either maternal or paternal exposure to ixekizumab cumulatively through 22 March 2019, were identified in the Eli Lilly Global Safety Database and described separately.Results One hundred and ninety-three ixekizumab-exposed pregnancies were identified. Maternal exposure occurred in 51.3% of pregnancies (clinical trials: n = 58; post-marketing: n = 41). The majority of paternal exposure pregnancies occurred in clinical trials (91 of 94). Live births were reported for 53.8 and 61.1% of known outcomes in maternal exposure pregnancies during clinical trials and post-marketing surveillance, respectively. No congenital malformations resulting from maternal exposure were reported in clinical trials: one case, not causally related to ixekizumab therapy, was recorded in the post-marketing setting.Conclusions This integrated safety analysis provides relevant information for clinicians treating patients with psoriasis, PsA, or axSpA with ixekizumab. No new safety signals were identified in patients receiving ixekizumab.